Promoting Climate Resilience in Building Construction Industry in Ghana - Asante Frimpong, Chrysogonus (International Journal of Global Sustainability, 2023)
This study reports the perspectives of building construction stakeholders on how they are promoting climate resilience. Using descriptive research design with a purposive sampling through online questionnaire and adapted version of Relative Importance Index (RII) on selected environmental benchmarks, the major findings are: a) there is more to be done to promote green construction; b) many stakeholders still hold on to carbon-intensive approach; c) underlying cause for this lack of migration to less carbon use appears to be attitudinal than complete lack of knowledge of climate mitigation; d) many construction firms lack internal management system to monitor climate mitigation benchmarks indices. Based on these findings, recommendation being made is that construction managers may need to link up with international conferences to enhance professional competencies in advanced technologies for mitigating building-related carbon emission, while Government offers subsidies and green construction certification to promote contractors’ awareness of climate resilience in building construction.